“We faced Mabvuto”: the state, African authorities and Nyasa women experiences of migration to Rhodesia, 1935 -1960s. - Mudeka, Ireen (Midlands State University, 2015)
Historians have primarily presented the history of African colonial migration as an exclusively male labor experience. Pioneering scholarship, which interrogated this male bias, mostly emphasized women’s internal on women’s cross border migration is gaining ground, focus remains contemporary. This article redirects attention by examining Nyasa Women’s migration to Southern Rhodesia, and argues that African women’s cross territorial mobility has roots going deep into the colonial era. The study begins in the 1930s, when the effects of migration to Zimbabwe first raised concern and ends in the mid 1960s, with the end of colonial rule in Nyasaland. In this era, women’s migration became particularly important in light of the official view of inter-colonial migration as a male terrain. Driven to migrate by socio-economic needs, the women confronted colonial and African authorities, whose economic interests and patriarchal perceptions justified efforts to deny them mobility. They thus fought against, resisted and subverted the system of control constituted by male officials, African household, village and chiefdom heads and ‘police-boys’.